Funções de correlação para uma cadeia de Ising decorada com spins Heisenberg numa estrutura diamante - Carvalho, Isaac Martins (2018)
One-dimensional systems with short-range interactions cannot exhibit a long-range order at nonzero temperature. However, there are some particular one-dimensional models, such as the Ising-Heisenberg spin models with a variety of lattice geometries, which exhibit unexpected behavior similar to the temperature-driven phase transition. Although these pseudo-transitions are not true temperature-driven transitions showing only abrupt changes or sharp peaks in thermodynamic quantities, they may be confused while interpreting experimental data. Here we consider the spin-1/2Ising-XYZ diamond chain in the regime when the model exhibits temperature-driven pseudo-transitions. We provide a detailed investigation of various correlation functions between distant spins that illustrate the properties of quasi-phases separated by pseudo-transitions. Inevitably, all correlation functions present evidence of pseudo-transitions, which are supported by analytical solutions, which have been rigorously investigated around the pseudo-critical temperature. It is worth to mention that the correlation functions between distant spins have an extremely large correlation length at pseudo-critical temperature.